2020
DOI: 10.1186/s12909-020-1992-1
|View full text |Cite
|
Sign up to set email alerts
|

Ready to collaborate?: medical learner experiences in interprofessional collaborative practice settings

Abstract: Background: Interprofessional collaborative practice (IPCP) offers great potential to improve healthcare. Increases in IPCP will require educating learners in authentic IPCP settings and will generate opportunities and challenges. Methods: In January 2015, we implemented an IPCP model called Collaborative Care (CC) for hospitalized adult medical patients. We explored learner perspectives regarding their educational experiences. We deductively coded transcripts from semi-structured interviews with medical learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…Interprofessional education research evidence provides a clear indication that it can improve collaborative attitudes/perceptions and knowledge/skills necessary for collaborative practice [35]. It also reinforces the union of medical students from different majors when studying together, such as clinicians, nurses, pharmacists, radiologists and health managers [36]. By solving complex clinical problems together, it encourages exchanges and interactions between students of different majors, thereby promoting the establishment and development of professional responsibility and professional leadership.…”
Section: Logical Relationships Between Different Types Of Student Engmentioning
confidence: 94%
“…Interprofessional education research evidence provides a clear indication that it can improve collaborative attitudes/perceptions and knowledge/skills necessary for collaborative practice [35]. It also reinforces the union of medical students from different majors when studying together, such as clinicians, nurses, pharmacists, radiologists and health managers [36]. By solving complex clinical problems together, it encourages exchanges and interactions between students of different majors, thereby promoting the establishment and development of professional responsibility and professional leadership.…”
Section: Logical Relationships Between Different Types Of Student Engmentioning
confidence: 94%
“…Interprofessional education research evidence provides a clear indication that it can improve collaborative attitudes/perceptions and knowledge/skills necessary for collaborative practice [37]. It also reinforces the union of medical students from different majors when studying together, such as clinicians, nurses, pharmacists, radiologists and health managers [38]. By solving complex clinical problems together, it encourages exchanges and interactions between students of different majors, thereby promoting the establishment and development of professional responsibility and professional leadership.…”
Section: Logical Relationships Between Different Types Of Student Engmentioning
confidence: 94%
“…Sixteen studies focused on interprofessional rounds, 21,22,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] of which 9 studies were either medium or highquality (Table 3). Reported benefits of this practice included a perceived increase in collaboration 22,62,65 and communication 21,22,57,60,65,66 among health care teams; a highquality time series study also reported earlier discharge times.…”
Section: Interprofessional Roundsmentioning
confidence: 99%
“…Interprofessional rounds may improve team collaboration and communication, and enhance discharge planning. 21,22,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] Moderate confidence…”
Section: Studies Contributing To the Review Findingmentioning
confidence: 99%
See 1 more Smart Citation